Evaluating the Implementation of the Conversation Starter Kit in Long Term Care - Sharon Kaasalainen RN, PhD; Tamara Sussman MSW, PhD; Maria Nicula BSc; Jack Lawrence BSc; Genevieve Thompson RN, PhD; Lynn McCleary RN, PhD; Abigail Wickson-Griffiths RN, PhD; John J. You MD, MSc (SAGE Publishing, 2021)
Introduction Advance care planning can improve the quality of life for residents in long-term care homes and reduce stress for families. However, care home staff and families often lack knowledge about advance care planning, making it especially difficult for residents with dementia to communicate their care plan wishes. A Conversation Starter Kit may increase advance care planning awareness among staff and families. Objectives This study evaluated an advance care planning intervention, the Conversation Starter Kit booklet, for use in long term care homes. Methods Data were collected at three long-term care homes in southern Ontario. We collected data from 55 residents who were able to make decisions on their own paired with 11 family members of these residents. We also collected data from 24 family members of residents who were unable to make decisions on their own. This study used a quasi-experimental, one group pre/post design. Quantitative surveys were administered before and after a three-month advance care planning intervention. An additional structured interview was completed at the end of the intervention period, which included both closed and open-ended questions to assess perceptions about the booklet's use or non-use. Results Residents reported more engagement in advance care planning after completing the Conversation Starter Kit booklet, particularly related to asking questions to health care providers about health care decisions. Family members reported feeling very certain that they would be able to make decisions on behalf of the resident but felt less certain after completing the booklet, implying the booklet raised their awareness of the types of decisions they might need to make, hopefully prompting them to be more prepared for decisions in the future. Conclusions An advance care planning intervention - The Conversation Starter Kit booklet - appears acceptable and easy to use for residents and family members/friends in long-term care and can improve resident engagement in advance care planning. Although using the booklet may decrease efficacy for decision making among family members of long-term care residents, it may highlight the importance of more actionable engagement in advance care planning among residents, their families/friends, and staff.